Functional foods and dietary supplements in the management of non-alcoholic fatty liver disease: A systematic review and meta-analysis - Wang, Lei-lei; Zhang, Pian-hong; Yan, Hui-hui (Frontiers in Nutrition, 2023)
Objective In this systematic review and meta-analysis, we aimed to clarify the overall effects of functional foods and dietary supplements in non-alcoholic fatty liver disease (NAFLD) patients. Methods Randomized controlled trials (RCTs) published in PubMed, ISI Web of Science, Cochrane library, and Embase from January 1, 2000 to January 31, 2022 were systematically searched to assess the effects of functional foods and dietary supplements in patients with NAFLD. The primary outcomes were liver-related measures, such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), and hepatic fibrosis and steatosis, while the secondary outcomes included body mass index (BMI), waist circumference (WC), triacylglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C). These indexes were all continuous variables, so the mean difference (MD) was used for calculating the effect size. Random-effects or fixed-effects models were used to estimate the mean difference (MD). The risk of bias in all studies was assessed with guidance provided in the Cochrane Handbook for Systematic Reviews of Interventions. Results Twenty-nine articles investigating functional foods and dietary supplements [antioxidants (phytonutrients and coenzyme Q10) = 18, probiotics/symbiotic/prebiotic = 6, fatty acids = 3, vitamin D = 1, and whole grain = 1] met the eligibility criteria. Our results showed that antioxidants could significantly reduce WC (MD: −1.28 cm; 95% CI: −1.58, −0.99, P < 0.05), ALT (MD: −7.65 IU/L; 95% CI: −11.14, −4.16, P < 0.001), AST (MD: −4.26 IU/L; 95% CI: −5.76, −2.76, P < 0.001), and LDL-C (MD: −0.24 mg/dL; 95% CI: −0.46, −0.02, P < 0.05) increased in patients with NAFLD but had no effect on BMI, TG, and TC. Probiotic/symbiotic/prebiotic supplementation could decrease BMI (MD: −0.57 kg/m2; 95% CI: −0.72, −0.42, P < 0.05), ALT (MD: −3.96 IU/L; 95% CI: −5.24, −2.69, P < 0.001), and AST (MD: −2.76; 95% CI: −3.97, −1.56, P < 0.0001) levels but did not have beneficial effects on serum lipid levels compared to the control group. Moreover, the efficacy of fatty acids for treating NAFLD was full of discrepancies. Additionally, vitamin D had no significant effect on BMI, liver transaminase, and serum lipids, while whole grain could reduce ALT and AST but did not affect serum lipid levels. Conclusion The current study suggests that antioxidant and probiotic/symbiotic/prebiotic supplements may be a promising regimen for NAFLD patients. However, the usage of fatty acids, vitamin D, and whole grain in clinical treatment is uncertain. Further exploration of the efficacy ranks of functional foods and dietary supplements is needed to provide a reliable basis for clinical application. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier: CRD42022351763.